Innovations In Early Childhood Education In The Millennial Era - Amirah Mawardi; Baharuddin Baharuddin (Proceeding International Seminar of Islamic Studies, 2019)
This study aims to describe new innovations in the world of education, especially on some new innovations in early childhood learning in the millennial era. In general, innovation in education can be described as the process of perfecting a product, or an existing process with the aim of making a positive change. If educational innovation is successfully adopted in early childhood learning, there will be changes, renewal and improvement in the quality of education, especially for educators in PAUD and other similar educational institutions. Learning Innovation in Early Childhood Education (PAUD) refers to Permendiknas (Minister of National Education Regulation)literature number 58 of 2009, which contains 5 (five) aspects that must always be developed in early childhood namely: 1). Development of religious and moral values, 2). Motor, 3). Cognitive, 4). Language, 5). Social emotional. By using the theory of innovation as well as a description of the characteristics and characteristics of education in the millennial era, it was concluded that educators in Early Childhood Education Institutions (PAUD) are expected to be able to apply learning innovations especially in applying 5 (five) aspects of child development according to Ministry of Education Regulation No. 58 of 2009 so that the vision and the development goals of Early Childhood Education (PAUD) can be achieved.